Self-Concept and Parenting Pattern of Parents in Children with Physical Disabilities of Early Deaf - Sulthon, Sulthon (THUFULA, 2023)
This research is based on the phenomenon of parents who have children with hearing impairments,they feel disappointed, ashamed and closed.This study aims to identify and understand the social symptoms of self-concept and parenting parents of deaf early childhood children. This study used a qualitative method with a qualitative descriptive approach which was carried out on 3 parents of deaf children at an early age who attended Special Schools (SLB) Sunan Prawoto, Sukolilo, Pati. The research results show that; 1) the self-concept of parents of deaf children at an early age is negative, assuming that their children are different, not according to expectations; 2) the parenting style given is more permissive in: (1) parent support parents do not foster, educate, and instill good values, (2) parental control behavior gives too much freedom and leeway to children without prohibitions and supervision, 3) psychological control does not provide warmth, affection, attention, and a sense of security for children. The contribution of this research is to provide knowledge, understanding, and awareness to parents about children as entrusted by God who must be grateful for any form so that self-concept becomes positive and can accept children and then provides democratic parenting, provides guidance and education is more proportional to developing the potential of children with disabilities so that independent in his life.